Zakat Obligasi dalam Perspektif Hukum Islam - Muhammad Taufan Djafri; Hendra Wijaya; Syamsul Rijal (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to determine the status of bonds in Islamic law, understand the Islamic law review of zakat on bonds, and find out how to calculate zakat on bonds in Islam. This research is library research using descriptive analysis techniques. The results of this research show that: (1) The status of bonds in Islam is halal and zakat is mandatory; (2) In reviewing Islamic law, scholars have different opinions regarding the issuance of zakat on bonds, the first opinion states that bonds are not subject to zakat because they contain elements of usury, while the second opinion states that zakat is required for bonds along with the interest. The second opinion is a strong opinion because conventional bonds require zakat to be issued on the nominal value of the bond itself at 2.5%. Meanwhile, the zakat that must be paid on sharia bonds, namely from the bond itself, both the bond and its profits, must pay 2.5% zakat; (3) How to calculate zakat on bonds in Islam, namely bonds at PT Bank Mandiri, zakat is calculated based on their nominal value, namely 1000 bonds times IDR 25,000 equals IDR 25,000,000 then 25,000,000 times the zakat rate (2.5%) the result is the same as IDR 625,000.